A hybrid simulator model for the control of catastrophic external junctional haemorrhage in the military environment. Issue 1 (January 2016) - Silverplats, Katarina; Jonsson, Anders; Lundberg, Lars
Abstract Catastrophic haemorrhage from extremity injuries has for a long time been the single most common cause of preventable death in the military environment. The effective use of extremity tourniquets has increased the survival of combat casualties, and exsanguination from isolated limb injuries is no longer the most common cause of death. Today, the most common cause of potentially preventable death is haemorrhage from the junctional zones, i.e. the most proximal part of the extremities, not amenable to standard tourniquets. Different training techniques to control catastrophic haemorrhage have been used by the Swedish Armed Forces in the pre-deployment training of physicians, nurses and medics for many years. The training techniques include different types of human patient simulators such as moulage patients and manikins. Preferred training conditions for the control of catastrophic haemorrhage include a high degree of realism, in combination with multiple training attempts. This report presents a new hybrid training model for catastrophic external junctional haemorrhage control. It offers a readily reproducible, simple and inexpensive opportunity to train personnel to deal with life threatening catastrophic junctional haemorrhage. In particular, this model offers an opportunity for non-medical military personnel in Sweden to practice control of realistic catastrophic haemorrhage, with multiple training attempts.